Byron’s bear and dwarf rabbits in the classroom: a review of animals against academic stress - Erren, Thomas C.; Glenewinkel, Florian; Wild, Ursula; Wallraff, Jonas; Lewis, Philip (Frontiers in Veterinary Science, 2025)
BackgroundCoping strategies for academic stress at different stages of human development are important. We address the hypothesis that human-animal interactions (HAI) in both non-therapy and therapy situations can help adults, adolescents and children cope with academic stress in universities and schools. We point to Lord Byron’s “pet” bear in the 19th century and to media reports of pets on the high-pressure academic campuses of Oxford and Cambridge as historical and current examples.MethodsWe review scientific literature concerning HAI and stress in university settings (exemplified via narrative information) and in the pre-university school environment (explored via systematic information). Media reports from Oxbridge underline the popularity of HAI.ResultsA pilot search returned n = 4 recent reviews and meta-analyses of studies from university settings that covered mental, cognitive, and physiological health outcomes. The synthesis of these studies suggests that HAI may have benefits for stress and anxiety with the optimal duration and frequency of HAI remaining open. Studies from pre-university settings also suggest a possible benefit in terms of reducing anxiety and salivary cortisol as an indicator of stress, but there are only a few studies on this topic (n = 3).ConclusionThere is potential for improved mental health outcomes through HAI in academic environments, but more research is needed to establish best practices.